Environmental Education and Cultural Studies: among erasures and new radicalisms - Shaula Maíra Vicentini de Sampaio (Universidade Federal do Rio Grande do Sul, 2019)
This article discusses the conflicting but potent (dis)encounters among the polymorphic fields of Environmental Education and Cultural Studies. It shows that much research from this articulation has been dedicated to printing erasures in discourses circulating in culture about nature and the environment. But what about when deconstructing is not enough? Recent debates about the environmental crisis, the Anthropocene, climate change and its social developments bring the need for new questions about the connections between culture and environment. Finally, it questions whether the political bias that has marked cultural studies since its emergence may contribute to the search for new radicalisms in Environmental Education.